Dr Skeletal Effects of Soy Isoflavone in Humans: Bone Mineral Density and Bone Markers - Rehan Haider (PT FORMOSA CENDEKIA GLOBAL, 2023)
The potential skeletal effects of soy isoflavones in humans have garnered significant interest owing to their structural resemblance to endogenous estrogen and their potential to impact bone health. This abstract provides a concise overview of the current understanding of the effects of soy isoflavones on bone mineral density (BMD) and bone markers. Numerous studies have investigated the relationship between soy isoflavone consumption and BMD. Some studies have suggested a positive association between soy isoflavone intake and BMD, particularly among postmenopausal women. Isoflavones may exert their effects through estrogen receptor-mediated pathways, potentially mitigating bone loss by reducing osteoclastic activity and promoting osteoblastic functions. However, conflicting results have been reported, with certain studies demonstrating no significant impact on BMD. In addition to BMD, bone markers such as serum osteocalcin, urinary deoxypyridinoline, and tartrate-resistant acid phosphatase have been evaluated to elucidate the mechanistic effects of soy isoflavones on bone metabolism. These markers provide insights into bone turnover, resorption, and formation. Clinical trials have reported mixed findings regarding the influence of soy isoflavones on bone markers, reflecting the complexity of their interaction with bone physiology